'You have to find the right words to be honest': nurturing relationships between teachers and parents of children with Special Educational Needs. Issue 3 (28th August 2021) - Solvason, Carla; Proctor, Samuel
Abstract : This article explores the views of a small group of teachers who specialise in supporting children with Special Educational Needs (SEN). Frequently literature exploring the relationship between parents and teachers of children with SEN uses language which is confrontational, even aggressive. This research, based within a specialist school in England, portrays the voices of the teachers themselves, presenting their perspective on creating relationships with, and supporting the parents of, children with SEN. Far from the language of antagonism portrayed in so many articles, the rich descriptions elicited through focus group discussion demonstrate relationships that are established upon sensitivity, understanding, kindness and care. Our data paint a picture of teachers who feel deeply for the emotional turmoil that many of their parents have suffered before reaching their door; and do all that is possible to hold them safely, while they acclimatise to the new 'normality' of their child accessing specialist provision.